Sleep disturbance in family caregivers of children who depend on medical technology. Issue 2 (26th October 2017) - Keilty, Krista; Cohen, Eyal; Spalding, Karen; Pullenayegum, Eleanor; Stremler, Robyn
Abstract : Objectives: Family caregivers of children who depend on medical technology (CMT) provide highly skilled care up to 24 hours per day. Sleep disruption places family caregivers at risk for poor health and related outcomes that threaten their long-term caregiving capacity. Few studies exist that have measured sleep in family caregivers, and most have relied entirely on subjective measures. Methods: In a prospective cohort study, family caregivers of CMT (n=42) and caregivers of healthy children (n=43) were recruited. Actigraphy data and a concurrent sleep diary were collected for 6 days/7 nights. Measures of sleep quality, depression, sleepiness, fatigue and quality of life were also administered. Results: Family caregivers of CMT averaged fewer hours of sleep per night (mean (SD)) (6.56 ± 1.4 vs 7.21 ± 0.6, p = 0.02) of poorer quality (7.75 ± 2.9 vs 5.45 ± 2.8, p < 0.01) than the control group. Three times as many family caregivers of CMT scored in the range for significant depressive symptomatology (12(33%) vs 4(10%), p = 0.01) and experienced excessive daytime sleepiness (16(38%) vs 5(12%), p < 0.01). Fatigue was also more problematic among family caregivers of CMT (22.12 ± 9.1 vs 17.44 ± 9.0, p = 0.02). Conclusions: Family caregivers of CMT are at risk of acute and chronic sleep deprivation, psychological distress and impaired daytime function that may threaten their capacity for sustained caregiving. Family caregivers of CMT may be important targets for screening for sleep disorders and the development of novel sleep-promoting interventions.